“It Gets a Bit Messy”: Norwegian Social Workers’ Perspectives on Collaboration with Police and Security Service on Cases of Radicalisation and Violent Extremism - Haugstvedt, Håvard (Terrorism and political violence, 2023)
Social workers are a part of the prevention efforts against radicalisation and violent extremism in the Nordic countries. While multi-agency cooperation is not new in Norway, municipal cooperation with the police security service is. This cooperation, particularly its unintended consequences with a specific focus on the securitisation of “soft professionals” in the public sector, has been scarcely researched. We address this gap with findings from a qualitative study based on seventeen individual in-depth interviews and two focus-group interviews with experienced social workers in Norway. Abbott’s theory of jurisdiction serves as our theoretical framework. Our findings suggest that social workers in some cases appear subordinate to law enforcement personnel. Further, the lack of clarity of roles and responsibilities raises ethical and professional dilemmas, especially regarding work transparency and client confidentiality, indicating an outside influence of security onto prevention work. An unintended consequence of this is the risk of lower levels of trust between prevention workers and their target group and a reduced ability to support at-risk individuals. Clarification of the roles and responsibilities of all partners involved in multi-agency PVE should be given attention from both policymakers and practitioners.